Dynamics of Soil Fertility Indicators in Protective Forest Plantations - Kotlyarova E.; Kuzmina О.; Kolesnichenko Е.; Melentiev A.; Chursin A. (E3S Web of Conferences, 2024)
The purpose of the work is to analyze the dynamics of soil fertility indicators under forest belts in comparison with the inter-belt space in the agricultural landscape due to soil transformation under the influence of adaptive landscape farming systems. A comparative analysis of the variability of soil fertility indicators in forest belts and agrocenoses revealed similar trends in its direction and intensity, which indicates the uniform nature of the soil-forming process. However, some features have been identified. The humus content in the soils of forest belts is on average slightly higher than in the space between the belts. This is caused by higher (2 times) rates of humus accumulation in them in the first period after the development of landscape farming systems. It is during this period that the weedy and rhizomatous stages of restorative succession of the herbaceous flora of forest belts are confined, characterized by a powerful vegetative mass of vegetation and, consequently, an equally significant supply of fresh organic matter, rich in nutrients, into the soil.